ʿAlāʾ al-Dīn al-Samarqandī’s Non-Realist Approach to Good (Ḥasan) and Bad (Qabīḥ): Moral Ontology in Sixth/Twelfth-Century Māturīdī Theology and Legal Theory - Hisashi Obuchi (22030832) (2024)
The Māturīdīs think that, without revealed law, human beings can grasp through speculative reasoning that some actions are good (ḥasan) and some are bad (qabīḥ). This article addresses the ontological aspect of such ethical rationalism. An analysis of the texts of legal theory shows that the sixth/twelfth-century Māturīdīs approached moral values in a non-realist way. Specifically, ʿAlāʾ al-Dīn al-Samarqandī (d. 539/1144?), who identifies himself as a true successor of Abū Manṣūr al-Māturīdī (d. 333/944), demonstrates that goodness (ḥusn) and badness (qubḥ) are neither real accidents nor divine command and prohibition; rather, “good” and “bad” just express one’s natural or rational approval and disapproval of objects and actions, and Prophetic law shapes some of the natural likes and dislikes. On this account, I conclude that al-Samarqandī’s view, shared by his contemporaneous fellow Māturīdīs such as Abū l-Thanāʾ al-Lāmishī (d. after 539/1144) and Najm al-Dīn al-Nasafī (d. 537/1142), challenges the current standard interpretations of the Māturīdī ethics as realism or divine command theory. Other Information Published in: Journal of Islamic Ethics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1163/24685542-20240008 Volume and issue information: Vol 8 No. 1-2 (2024): December 2024